Glutathione prevents ethanol induced gastric mucosal damage and depletion of sulfhydryl compounds in humans. Issue 2 (February 1993) - Loguercio, C; Taranto, D; Beneduce, F; del Vecchio Blanco, C; de Vincentiis, A; Nardi, G; Romano, M
Abstract : Whether parenteral administration of reduced glutathione prevented ethanol induced damage to and depletion of sulfhydryl compounds in the human gastric mucosa was investigated. Ten healthy volunteers underwent endoscopy on three separate occasions. Gastric mucosal damage was induced by spraying 80% ethanol on to the gastric mucosa through the biopsy channel of the endoscope. The gastric mucosal score, total sulfhydryls, glutathione, and cysteine were evaluated in basal conditions and after ethanol administration with and without pretreatment with parenteral glutathione. Glutathione significantly decreased the extent of ethanol induced macroscopic injury to the mucosa of the gastric body and antrum. Glutathione's protective effect is associated with appreciable inhibition of ethanol induced depletion of gastric sulfhydryl compounds. This is the first report of protection against ethanol induced gastric mucosal damage by a sulfhydryl containing agent in humans.